MGMT epimutations and risk of incident cancer of the colon, glioblastoma multiforme, and diffuse large B cell lymphomas - Oleksii Nikolaienko; Garnet L. Anderson; Rowan T. Chlebowski; Su Yon Jung; Holly R. Harris; Stian Knappskog; Per E. Lønning (Clinical Epigenetics)
Abstract Background Constitutional BRCA1 epimutations (promoter hypermethylation) are associated with an elevated risk of triple-negative breast cancer and high-grade serous ovarian cancer. While MGMT epimutations are frequent in colon cancer, glioblastoma, and B-cell lymphoma, it remains unknown whether constitutional MGMT epimutations are associated with risk of any of these malignancies. Methods We designed a nested case–control study, assessing potential associations between MGMT epimutations in blood from healthy individuals and subsequent risk of incident cancer. The study cohort was drawn from postmenopausal women, participating in the Women’s Health Initiative (WHI) study, who had not been diagnosed with either colon cancer, glioblastoma, or B-cell lymphoma prior to study entry. The protocol included n = 400 women developing incident left-sided and n = 400 women developing right-sided colon cancer, n = 400 women developing diffuse large B-cell lymphomas, all matched on a 1:2 basis with cancer-free controls, and n = 195 women developing incident glioblastoma multiforme, matched on a 1:4 basis. All cancers were confirmed in centralized medical record review. Blood samples, collected at entry, were analyzed for MGMT epimutations by massive parallel sequencing. Associations between MGMT methylation and incident cancers were analyzed by Cox proportional hazards regression. Results Analyzing epimutations affecting the key regulatory area of the MGMT promoter, the hazard ratio (HR) was 1.07 (95% CI 0.79–1.45) and 0.80 (0.59–1.08) for right- and left-sided colon cancer, respectively, 1.13 (0.78–1.64) for glioblastoma, and 1.11 (0.83–1.48) for diffuse large B-cell lymphomas. Sensitivity analyses limited to subregions of the MGMT promoter and to individuals with different genotypes of a functional SNP in the MGMT promoter (rs16906252), revealed no significant effect on HR for any of the cancer forms. Neither did we observe any effect of rs16906252 status on HR for any of the cancer forms among individuals methylated or non-methylated at the MGMT promoter. Conclusions Constitutional MGMT promoter methylation in normal tissue is not associated with an increased risk of developing colon cancer, glioblastoma, or B-cell lymphoma.